AIP Mutation Identified in a Patient with Acromegaly Caused by Pituitary Somatotroph Adenoma with Neuronal Choristoma - Nishizawa, H.; Fukuoka, H.; Iguchi, G.; Inoshita, N.; Yamada, S.; Takahashi, Y. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Pituitary adenoma with neuronal choristoma (PANCH) is a rare condition that includes ganglion cells and GH-producing tumor that is characterized by sparsely granulated somatotroph cell type. However, the pathophysiology of this condition remains to be elucidated. We report a case of 46-year-old woman with acromegaly caused by PANCH. The patient had a large and invasive macroadenoma that was resistant to preoperative therapy with somatostatin analogue (SSA) and dopamine agonist. Histological examination showed typical diffuse, chromophobe-type adenoma containing ganglion cells, and sparsely granulated somatotroph cell type, which were consistent with PANCH. Genetic analysis showed heterozygous germline missense mutation in the AIP gene that results in Y261X amino acid substitution. The clinical characteristics of acromegaly associated with AIP mutations are reportedly macroadenomas with tumor extension and invasion, lower decreases in GH and IGF-I and less tumor shrinkage with SSA treatment, and sparsely granulated somatotroph cell type, which are comparable with those observed in PANCH. Taken together, the mutation in AIP gene may explain the clinical characteristics and pathogenesis of PANCH.
Keywords: AIP; mutation; PANCH; acromegaly; octreotide